2007
DOI: 10.5558/tfc83515-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender representation on Canadian forest sector advisory committees

Abstract: managers have introduced new processes and legal requirements to incorporate public interest and values in the management of Crown lands. The advisory or citizen committee has become a key tool among these. According to Parkins et al. (2006) "these initiatives and legislative requirements indicate a shift toward place-based public participation in the management of Canada's public forests." 3 This shift is not unique to forestry. In all aspects of environmental management, a shift from sector-based to plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Instead, as HPCF became more driven to gain higher profits, more women gravitated toward the society where activities focused on forest and watershed protection, ecosystem-based forest development, employment, research, and public education. This self-selection resulted in both social and spatial segregation and reproduced gender norms around resource extraction and environmental protection that have been long-standing in Canada (Reed and Varghese 2007). In summary, although social learning was occurring at HPCF and KICODA, opportunities and outcomes were not evenly shared.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Instead, as HPCF became more driven to gain higher profits, more women gravitated toward the society where activities focused on forest and watershed protection, ecosystem-based forest development, employment, research, and public education. This self-selection resulted in both social and spatial segregation and reproduced gender norms around resource extraction and environmental protection that have been long-standing in Canada (Reed and Varghese 2007). In summary, although social learning was occurring at HPCF and KICODA, opportunities and outcomes were not evenly shared.…”
Section: Discussionmentioning
confidence: 79%
“…In both postindustrial and developing countries, researchers have demonstrated that participation in forestry decision making has been characterized by a gender order that privileges men's contributions to forestry (Reed 2010b), constrains women's participation in forestry management (Agarwal 2010, and ultimately contradicts the inclusive intentions of collaborative forest governance (e.g., Reed and Varghese 2007, Coulibaly-Lingani et al 2011, McDougal et al 2013a). Hence, we highlight gender as a central axis of social differentiation.…”
Section: Literature Review and Analytical Frameworkmentioning
confidence: 99%
“…Data on women in the primary sector are notoriously poor and rarely give insight into the wage and skill levels of women's employment (Reed, 2003a;Mills, 2006). Studies on women's perceptions of, and involvement in, resource management in Northern contexts are even less forthcoming (for exceptions, see Davidson and Black, 2001;Reed and Varghese, 2007). Moreover, Reed and Christie further point out that 'while gender remains one of the key axes of inequality scrutinized by environmental scholars of the Third World, researchers focused on problems in First World settings continue to omit gender (e.g.…”
Section: Natural Resource Scholarship: Why Gender Mattersmentioning
confidence: 93%
“…1 Ensuring that a broad range of needs and values are included in their processes is central to that goal (Agarwal 2010a). However, the engagement of communities in natural resource management does not inherently address inequalities based on gender and other forms of social diff erence (Reed and Varghese 2007). More broadly, the gender composition of public bodies can infl uence how they function and the decisions they make.…”
Section: Introductionmentioning
confidence: 99%
“…These are based on the diff erent roles, responsibilities, and experiences that men and women have within the community in relation to the natural environment (Mikkelsen 2005;Varghese and Reed 2012). For example, Reed and Varghese (2007) show that men are more likely to associate the environment with utilitarian values, whereas women convey stronger support for its intrinsic value. This does not imply that women's perspectives on the environment are homogenous; rather, that gender is one of many social structures that interact to infl uence the perspectives expressed within resource management.…”
Section: Introductionmentioning
confidence: 99%